Pedagogical tact as a component of a teacher’s moral culture - Kolokolnikova, Zulfiya U.; Lobanova, Olga B.; Gazizova, Tatiana V.; Kolesnikova, Tatyana A. (Opción, 2019)
The research objective was to describe the phenomenon of pedagogical tact in the context of the cultural and moral traditions of Russian and foreign pedagogical practices. The authors used comparative historical analysis of scientific-pedagogical and historical-pedagogical sources, chronological and comparative methods, and generalization of historical and pedagogical data. According to deontological approach, pedagogical tact is a professional agreement on teacher’s standards of conduct, while the moral-cultural approach views pedagogical tact as a component of teacher’s moral culture and manners. Thus, there is a contradiction in these interpretations of pedagogical tact, which is aggravated in Russia by standardization of pedagogical activity.